Knowledge and Attitudes Toward Erosive Tooth Wear Among Dental Professionals in Saudi Arabia: Life Sciences -Dentistry - Abdulrahman, Somaya; Basalama, Fatmah; Alsulami, Amjad; Majrashi, Bashayer; Baeisa, Bashaier; Alharbi, Amal; Abdouh, Ismail (International Journal of Life Science and Pharma Research, 2023)
Tooth erosion is the loss of tooth structure caused by chemical dissolution without the involvement of oral bacteria. Thisstudy aimed to assess the knowledge and attitudes about erosive tooth wear among dental professionals in Saudi Arabia. This crosssectionalstudy involved 201 dental students and dentists in Saudi Arabia. Data were collected by a questionnaire adapted from a previousstudy designed to assess knowledge of and attitudes about dental erosion. SPSS software was used to analyze the data, along with t-testand ANOVA. The total knowledge score had a mean of 11.47 (standard deviation [SD]=2.14). Most participants (96.52%) know thaterosive tooth wear may lead to pain and sensitivity. However, only 36.82% know that drinking a whole bottle of soda in several sittingsrather than just one sitting decreases the risk of erosive tooth wear. The total knowledge score was not significantly different aboutgender (p=0.102), marital status (p=0.255), qualification (p=0.513), region (p=0.249), or nationality (p=0.495). The total attitude score wasmoderate and ranged from a mean of 3.21 with an SD of 1.43 for "I think prevention is better than a cure" to a mean of 4.12 with an SDof 1.48 for "I am concerned with whether or not drinks I consume are acidic." Knowledge about dental erosion among dentalprofessionals in Saudi Arabia is better than moderate, while attitudes about dental erosion were moderate. It is recommended for dentalprofessionals to have more instruction on dental erosion topics to improve their knowledge. Future studies are needed using a randomsample to achieve more generalizable results.